2013
DOI: 10.1371/journal.pone.0081323
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Characteristics of the Sailfish (Istiophorus platypterus) and Swordfish (Xiphias gladius) in Gliding Postures at Their Cruise Speeds

Abstract: The sailfish and swordfish are known as the fastest sea animals, reaching their maximum speeds of around 100 km/h. In the present study, we investigate the hydrodynamic characteristics of these fishes in their cruise speeds of about 1 body length per second. We install a taxidermy specimen of each fish in a wind tunnel, and measure the drag on its body and boundary-layer velocity above its body surface at the Reynolds number corresponding to its cruising condition. The drag coefficients of the sailfish and swo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 48 publications
(43 reference statements)
1
24
0
Order By: Relevance
“…Surprisingly, the function of this structure is still controversial (Nakamura, 1983;Frazier et al, 1994). The rostrum has been hypothesized to improve hydrodynamics by reducing drag (Wisner, 1958;Ovchinnikov, 1970;Aleyev, 1977; but see Sagong et al, 2013), to be used for defense (as evidenced by rostral fragments found embedded in large predators; Fierstine, 1997;Fierstine et al, 1997) and to be used to strike, immobilize or dismember prey before ingestion, thereby facilitating feeding (Gudger, 1940;Talbot and Penrith, 1964;Scott and Tibbo, 1968). Although it is certainly possible that the elongated rostrum may have been selected for multiple roles, substantial evidence from stomach contents and recent field observations strongly support the latter feeding-related hypothesis (Scott and Tibbo, 1968;Stillwell and Kohler, 1985;Frazier et al, 1994;Shimose et al, 2007;Domenici et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the function of this structure is still controversial (Nakamura, 1983;Frazier et al, 1994). The rostrum has been hypothesized to improve hydrodynamics by reducing drag (Wisner, 1958;Ovchinnikov, 1970;Aleyev, 1977; but see Sagong et al, 2013), to be used for defense (as evidenced by rostral fragments found embedded in large predators; Fierstine, 1997;Fierstine et al, 1997) and to be used to strike, immobilize or dismember prey before ingestion, thereby facilitating feeding (Gudger, 1940;Talbot and Penrith, 1964;Scott and Tibbo, 1968). Although it is certainly possible that the elongated rostrum may have been selected for multiple roles, substantial evidence from stomach contents and recent field observations strongly support the latter feeding-related hypothesis (Scott and Tibbo, 1968;Stillwell and Kohler, 1985;Frazier et al, 1994;Shimose et al, 2007;Domenici et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although the rostrum in billfishes is mechanically suited to function as a feeding weapon, it may serve other functions as well. For example, it is hypothesized that turbulence created by the rostrum could delay the point of separation reducing form drag on the billfish body (Wisner, ; Ovchinnikov, ; Aleyev, ), although a recent study found no support for overall drag reduction when modeling different rostrum lengths in two billfish species (Sagong et al, ). Even if the rostrum does not have an impact on overall body hydrodynamics, it could provide a hydrodynamic advantage during feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Structures that project from the epidermis into the environment provide a hydrodynamic function in various groups of fishes (Blake, 1983). One of the most important factors in determining hydrodynamic drag is the boundary layer flow surrounding a fish, due to its effects on friction drag and flow separation (Sagong et al, 2013). Scales, spiny projections and rough surfaces protruding from the epidermis of fishes may act to stabilize the boundary layer (Webb, 1975;Bushnell & Moore, 1991), thereby helping to reduce hydrodynamic drag during swimming by generating vortices around the bodies of fishes to influence flow (Bone, 1972;Fish, 1998).…”
Section: N T E R S P E C I F I C C O M Pa R I S O N Smentioning
confidence: 99%
“…In teleosts, it is thought that the cteni of ctenoid scales produce micro-turbulence as the fish moves through the water (Fish, 1998). Adult I. platypterus are described as having V-shaped protrusions in their skin that point posteriorly (Nakamura, 1985;Sagong et al, 2008Sagong et al, , 2013. These protrusions produce paired vortices that create low and high shear stresses which, as they interact with vortices induced from adjacent protrusions, affect the level of drag (Sagong et al, 2008).…”
Section: N T E R S P E C I F I C C O M Pa R I S O N Smentioning
confidence: 99%